Evaluation of rheumatoid arthritis and connective tissue disease-related interstitial lung disease with pulmonary physiologic test, HRCT, and patient-based measures of dyspnea and functional disability - TOPÇU, ATAKAN; İNANÇ, GÜZİDE NEVSUN; DEMİR, MERYEM; KARAKURT, SAİT; ALACA TOPÇU, ZEYNEP (SPRINGER LONDON LTD, 2021)
Objectives We aim to investigate the relationship between pulmonary function and imaging parameters with symptom-related patient-reported outcome measures (PROs). Method We included 65 patients of rheumatoid arthritis (RA) and connective tissue disease (CTD) with and without interstitial lung disease (ILD) into this cross-sectional study. We evaluated the relationship between FVC, DLco, and PROs and compared to HRCT findings. PROs included visual analogue scale for breathing, modified Borg scale, medical research council dyspnea scale, St. George's respiratory questionnaire (SGRQ), Leicester cough questionnaire, and Short Form 36 quality of life (SF-36 QoL). Results The mean age was 57.4 +/- 9.7 and 61.9% (39/65) of patients had an established ILD. In RA-ILD group, SGRQ score was higher (p < 0.001) and SF-36 physical functioning score was lower (p = 0.02) than CTD-ILD group. In RA group, there was a significant correlation between FVC and SF-36 role functioning/physical score (r = 0.724, p = 0.012). In CTD group, SF-36 general health score was correlated with both FVC (r = 0.441, p = 0.045) and DLco (r = 0.485, p = 0.035), and also SF-36 physical functioning score was correlated with FVC (r = 0.441, p = 0.040). PROs were found to be similar between ILD and non-ILD patients. SF-36 QoL total and SGRQ outcomes were worse in non-ILD group. Conclusions We concluded that PROs could be used to evaluate health-related quality of life (HRQoL) in RA- or CTD-related ILD. The physical health determinants of HRQoL are measurably worse in RA-ILD patients than in CTD patients. But, PROs may not be very helpful in differentiating patients with cough and/or shortness of breath due to ILD or non-ILD causes in RA/CTD.
Keywords: Connective tissue disease; Interstitial lung disease; Patient-reported outcome measures; Rheumatoid arthritis; Warrick score